? How do you develop your strategic thinking skills - Abdel Hussein, Soumia Maan (Journal of Economic, Administrative and Legal Sciences, 2018)
The study aimed to adopt the methods and ways leading to improve the eligibility and abilities of strategic thinking persons in way that enabling them to make the sound decision – making with substantiate scientific method, the descriptive study method depended on scientific resources consistent with the specialization nature to be studded and the objective aiming to be reached and in away ensure adding new knowledge in the area, and the studier comes up with a number of results amongst: applying the strategic thinking approach leading to develop the labors feeling with affiliation and the institutional devotion also leads to deep rooting the strategic thinking culture to motivate thinking and mental energies for the labors towards innovation and accepting the change. The researcher opines to set a collection of recommendations, amongst at the institutional level and the other to develop the skills of the strategic thinker, amongst designing training and directive units aimed to develop the skills of the strategic thinking for the mangers working in the institution, and the attempt to spread the innovation and challenge culture among the labors in away enhancing the competition spirit and the desire of change for them.
Keywords: strategic thinking; creative thinking; environmental sensing; foreseeing the future; strategic decision